Case study of SME'S family business: Issues in succession and conflict - Hashim, Norashidah; Deraman, Norita; Mohamad, Armanurah (Universiti Utara Malaysia, 2011)
The case focuses on the management of family own business by Era Edar Sdn. Bhd. as SME and Bumiputera company in homeopathy and alternative medicine.Dr. Azizan and Dr. Hamsiah as the founder of the company have confronted many issues and conflicts at early start-up and expansion stage of this family business.This business was set up intentionally as family business and has went through the succession process to the second generation although one of the founder still maintain her role in management and ownership of the company.Not only the late Dr. Azizan and Dr Hamsiah have well planned for start-up and growth of the company but also family planned to have twelve children for the purpose of family business.Their famous product EXAMO CKM 500, was formulated by Dr. Azizan has become synonym to this company.Dr. Hamsiah has confronted many challenges and tribulation in positioning Era Edar Marketing Sdn. Bhd. and KUSDA as a group of company to be known by the Malaysian society as today.The study highlighted several conflicts including communication, family relation, jealousy, and strategy that has been taken by the founder to overcome the problems. This case also highlighted the succession plan by the founders and there was also element of culture in the succession plan.Thus, this case study focuses on the management of conflicts and succession that experienced by Dr. Hamsiah as the spouse and the founder of this company.